Missed Opportunities: Could a U.S.‐Russian Dialogue on Asia Pacific Have Prevented the New Cold War?. Issue 4 (27th December 2018) - Suslov, Dmitry
Abstract : A U.S.‐Russian dialogue on the Asia Pacific could have become a vital pillar of cooperation and helped sustain the bilateral relations through their deterioration in 2011 and especially since 2014. This is due to the importance of the Asia Pacific to both Russia and the United States, the lower incidence of serious contradictions between them in this region compared to Europe and the Post‐Soviet space, as well as the existence of common interests. However, this opportunity was missed as the Asia Pacific became instead another theater of U.S.‐Russian new systemic confrontation. Nonetheless, the two sides might still benefit if they succeed in separating their relations in the Asia Pacific from the general bilateral confrontation. Russia can create a favorable environment to continue the role of independent power center, help reduce polarization in the region, and prevent unnecessary tensions between the United States and its Asian allies and partners.